Pengaruh promosi penjualan dan kualitas produk terhadap keputusan pembelian mobil wuling confero di Surabaya - Hidayat, Arif Firmansyah; Untarini, Nindria (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study analyzes the effect of sales promotion and product quality on the decision to buy a wuling confero car in Surabaya. This research is quantitative. Questionnaires were distributed offline. The questionnaire uses a Likert scale. The sampling technique used is judgmental sampling with a total of 220 respondents. The statistical analysis used is multiple linear regression using SPSS. The results of this study indicate that sales promotions affect purchasing decisions and product quality influences purchasing decisions.